Cerita Pangeran Kornel dalam Perspektif Sastra dan Sejarah - Danan Darajat; Dedi Koswara; Retty Isnendes (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This article is motivated by ambiguity about a famous Cadas Pangeran road construction figure, Prince Surianagara Kusumahdinata or Prince Kornel. The approaches used in this article are descriptive and historical methods, literature review techniques, documentation studies, and interviews. The article aims to find out: (1) the character of Prince Kornel from a literary perspective; (2) the character of Prince Kornel from a historical perspective; (3) the synchronization of Prince Kornel's character in literature and history. The results show that the character of Prince Kornel in literature and history is not significantly different. The difference is that there is imagination in literature to build certain atmospheres that make the story more alive, and in history, it is based on existing historical facts. In addition, the character of Prince Kornel has a correlation viewed from matters relating to literature and history. The conclusion is that the story of Prince Kornel in literature is produced by historical events and the community's oral tradition about Prince Kornel that spread in Sumedang Regency. It can be said that the story of Prince Kornel from literary and historical perspectives is interconnected and influences each other.